2023
DOI: 10.3390/diagnostics13050848
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Salusins in Systemic Sclerosis—A Cross-Sectional Study

Abstract: Background: Systemic sclerosis (SSc) is a connective tissue disease manifesting with progressive fibrosis of the skin and internal organs. Its pathogenesis is strictly associated with vascular disfunction and damage. Salusin-α and salusin-β, endogenous peptides regulating secretion of pro-inflammatory cytokines and vascular smooth muscle proliferation, may potentially play a role in SSc pathogenesis. Objectives: The aim of this study was to assess the concentration of salusins in sera of patients with SSc and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Recent studies have shown how vast and ever-expanding the field of biomarkers is in SSc. Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown how vast and ever-expanding the field of biomarkers is in SSc. Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
“…Biomarkers will become increasingly important in research and, consequently, in the diagnosis and therapeutic approach to SSc [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Several studies have demonstrated the involvement of at least 240 pathways and numerous dysregulated proteins in the pathogenesis of SSc, so the field of biomarkers in this disease is complex and evolving [30][31][32][33][34][35][36][59][60][61][62][63][64][65][66][67]. Cytokeratin 17 (CK17), marginal zone protein B1 (MZB1), and leucine-rich α2-glycoprotein-1 (LRG1) appear to be potential biomarkers for SSc, with CK17 negatively associated with disease severity and higher values of CK17 protective [37,[59][60][61][62][63][64][65][66][67].…”
Section: Biomarkers In Systemic Sclerosismentioning
confidence: 99%
See 3 more Smart Citations